2022
DOI: 10.3389/fcvm.2022.922441
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide and its precursors in relation to blood pressure: A mendelian randomization study

Abstract: ObjectivePrevious studies have demonstrated that trimethylamine N-oxide (TMAO) and its precursors, including choline, betaine, and carnitine, are closely associated with blood pressure (BP) changes. Nevertheless, with the limitation of reverse causality and confounder in observational studies, such a relationship remains unclear. We aimed to assess the causal relationship of TMAO and its precursors with BP by the Mendelian Randomization (MR) approach.MethodIn this study, two-sample MR was used to reveal the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The Mendelian Randomization approach showed that an increase in TMAO 1 unit was associated with a 1SD increase in systolic blood pressure in mmHg. 67 TMAO-related lipid and glucose metabolism could contribute to hypertension. 59 Additionally, TMAO could aggravate angiotensin II-induced vasoconstriction, resulting in hypertension and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The Mendelian Randomization approach showed that an increase in TMAO 1 unit was associated with a 1SD increase in systolic blood pressure in mmHg. 67 TMAO-related lipid and glucose metabolism could contribute to hypertension. 59 Additionally, TMAO could aggravate angiotensin II-induced vasoconstriction, resulting in hypertension and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In several large independent clinical cohorts, plasma TMAO levels were shown to be associated with the risk of CAD morbidity and long-term mortality and thus predictors of cardiovascular risk (Tang et al, 2013;Wang et al, 2014). However, in the MR study, there is no direct causal relationship between TMAO and CAD, but a suggestive association of genetically increased choline with a higher risk of T2DM (Jia et al, 2019) and the same effect of TMAO and carnitine with systolic BP (Wang et al, 2022). Butyrate is a short-chain fatty acid (SCFA) produced by the metabolism of intestinal microflora, which has been proved to be a protective metabolite for CAD in contrast to TAMO (Hu et al, 2022).…”
Section: Introductionmentioning
confidence: 88%
“…Only three MR studies were performed focusing on the role of TMAO. The first one assessed the association of gut-microbiota-related metabolites and cardiometabolic health [49]; the second was in relation to Alzheimer's disease [50]; and the most recent was in relation to blood pressure [51]. In the study of Jia et al, they did not find a significant association of genetically predicted higher TMAO levels with cardiometabolic disease (including T2D, atrial fibrillation, CAD, MI, stroke, and CKD).…”
Section: Tmao In Genetic Studiesmentioning
confidence: 99%